2018
DOI: 10.4103/ijstd.ijstd_44_16
|View full text |Cite
|
Sign up to set email alerts
|

Measles, mumps, and rubella vaccine in genital warts: A case report of two patients

Abstract: Genital warts have a big psychological impact on the affected individuals, as the treatment requires time and multiple sessions at a time. They can also increase the chances of acquiring other sexually transmitted diseases. Various treatment options are available including the topical application of imiquimod, podophyllin, trichloroacetic acid application, cryotherapy, and radiofrequency cautery. However, all of these require multiple sessions, and chances of recurrences are high. Some of them also have multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Regarding side effects in Group B, this study showed that pain on the day of injection occurred in only 16.7% of patients in Group B. Their pain was tolerable and did not affect the compliance of patients to continue the treatment protocol; this was in agreement with several previous studies (9,11,23,25). In our study, flu-like symptoms were not reported in Group B, and this was in agreement with the findings by Na et al (21).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding side effects in Group B, this study showed that pain on the day of injection occurred in only 16.7% of patients in Group B. Their pain was tolerable and did not affect the compliance of patients to continue the treatment protocol; this was in agreement with several previous studies (9,11,23,25). In our study, flu-like symptoms were not reported in Group B, and this was in agreement with the findings by Na et al (21).…”
Section: Discussionsupporting
confidence: 93%
“…Although MMR vaccine has shown promising results in previous reports when used in common, multiple, and recalcitrant cutaneous warts (11,(20)(21)(22)(23)(24), data on its efficacy in plantar warts are relatively sparse in published literature.…”
Section: Discussionmentioning
confidence: 99%
“…One case study described the use of measles, mumps, and rubella (MMR) vaccine in therapy of genital warts ( Figure 1, Table 1). 7 vaccine has been successfully used in the treatment of genital warts.…”
Section: Methodsmentioning
confidence: 99%
“…In the last several years, intralesional immunotherapy has shown promising efficacy in the treatment of anogenital warts and include the use of following therapeutic agents: Bacille Calmette-Guérin vaccine and tuberculin purified protein derivative, mumps vaccine, Candida albicans antigen, Mycobacterium welchii vaccine, Mycobacterium indicus pranii vaccine, MMR vaccine, Trichophyton skin test antigen, etc 1,[7][8][9][10][11][12][13][14][15][16]. Overall, the results of immunotherapy have been highly variable amongst individuals but the method is highly promising because of its activity beyond the injected wart and therefore, a significant number of patients are cured of distant warts.…”
mentioning
confidence: 99%
“…Several diseases have been eradicated with the use of vaccines, such as smallpox in humans and rinderpest on animals, along with the near eradication or successful prevention of other viral or bacterial infections [34,35]. However, the development of vaccines against fungal infections remains a challenge, in part due to a lack of knowledge about the mechanisms of protective immunity against fungal infections and the genetic complexity of fungi [5].…”
Section: Vaccine and Immunotherapymentioning
confidence: 99%